Investigation on the impact of nano MgO addition on dielectric properties and space charge behavior of epoxy resin AlN nanocomposites. (19th February 2021) - Nagaraju, Guvvala; Sarathi, Ramanujam
Abstract: Epoxy nano composites were fabricated with the incorporation of nano AlN and MgO fillers to investigate their dielectric and space charge properties. Epoxy AlN nanocomposites with the addition of nano MgO have shown lower permittivity with reduced tan δ, good space charge behaviour, during poling period. Higher wt% of AlN in epoxy resin exhibited higher permittivity. The nanocomposites with AlN nanofiller have revealed higher space charge accumulation than on addition of MgO nano filler. Also, the addition of nanofillers to the base polymer has led to enhanced space charge decay performance compared to the base matrix.